Expanding the Data Capacity of QR Codes Using Multiple Compression Algorithms and Base64 Encode/Decode - Abas, Azizi; Yusof, Yuhanis; Kabir Ahmad, Farzana (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
The Quick Response (QR) code is an enhancement from one dimensional barcode which was used to store limited capacity of information. The QR code has the capability to encode various data formats and languages. Several techniques were suggested by researchers to increase the data contents. One of the technique to increase data capacity is by compressing the data and encode it with a suitable data encoder. This study focuses on the selection of compression algorithms and use base64 encoder/decoder to increase the capacity of data which is to be stored in the QR code. The result will be compared with common technique to get the efficiency among the selected compression algorithm after the data was encoded with base64 encoder/decoder.